How Deep Is Your Love? A Quantitative Spatial Analysis of the Transatlantic Trade Partnership - Oliver Krebs; Michael P. Pflüger (Institute for the Study of Labor (IZA), 2015)
This paper explores the quantitative consequences of transatlantic trade liberalization envisioned in a Transatlantic Trade and Investment Partnership (TTIP) between the United States and the European Union. Our key innovation is to develop a new quantitative spatial trade model and to use an associated technique which is extraordinarily parsimonious and tightly connects theory and data. We take input-output linkages across industries into account and make use of the recently established World Input Output Database (WIOD). We also explore the consequences of labor mobility across local labor markets in Germany and the countries of the European Union. We address the considerable uncertainties connected both with the quantification of non-tariff trade barriers and the outcome of the negotiations by taking a corridor of trade liberalization paths into account.
Keywords: F10; F11; F12; F16; 330; international trade and trade policy; factor mobility; intermediate inputs; sectoral interrelations; transatlantic trade; TTIP